Conflict and shifting boundaries in the gig economy : an interdisciplinary analysis - Page-Tickell, Rebecca; Yerby, Elaine (Emerald Publishing Limited, 2020)
Using an interdisciplinary lens, this book innovatively explores the conflicts and shifting boundaries in organisational, professional, legal and economic structures, caused by the rise of the gig economy. The dynamic structural model of the gig economy is introduced to interrogate the inner workings of the amorphous gig economy at the Macro, Meso and Micro levels of analysis. Conflict and Shifting Boundaries in the Gig Economy examines a range of tensions and issues, including; The future of trade unions in the gig economy Employment status and contractual arrangements Talent management in the gig economy Employee voice and whistleblowing Career choices and organisational attractiveness Trajectory and impact at macro economic levels. Organisational examples and a focus on the perspective of those engaged in gig work introduce new insights and research questions on the current and future challenges posed by the gig economy, alongside using the structural dynamic model as a tool to understand actors and organisational experiences and build appropriate interventions.
Chapter 1: Understanding conflict and shifting boundaries in the gig economy through the Dynamic Structural model / Elaine Yerby and Rebecca Page-Tickell Section 1: Macro Analysis -- Chapter 2: Defining the employee in the gig economy: untangling the web of contract / Barry Collins -- Chapter 3: The shifting boundaries of capitalism and the conflict of surplus value appropriation within the gig economy / Shampa Roy-Mukherjee and Michael Harrison -- Chapter 4: Presence and pretence - trade unions and the gig economy / Rebecca Page-Tickell and Jude Ritchie Section 2: Meso Analysis -- Chapter 5: The dis-evolution of strategic HRM in the gig economy from talent management to supply chain manager / Andrew Boocock, Elaine Yerby and Rebecca Page-Tickell -- Chapter 6: Worker and organisational protection: the future of whistleblowing in the gig economy / Catherine Hobby -- Chapter 7: Gig Economy and the transformation of professional boundaries in Healthcare / Ali Naghieh Section 3: Micro Analysis -- Chapter 8: Evolutionary mismatch and misbelief impacts on participants in the gig economy / Rebecca Page-Tickell, Jude Ritchie and Therese Page-Tickell -- Chapter 9: Frayed careers in the gig economy - rhythms of career privilege and disadvantage / Elaine Yerby -- Chapter 10: Status quo, renewal and decline in the gig economy / issues of agency, voice and identity / Elaine Yerby and Rebecca Page-Tickell.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Temporary employment -- Economic aspects; Organizational behavior; Business & Economics -- Human Resources & Personnel Management; Employment & unemployment